Evolving Sustainable Material Culture (SMC): Emerging Trends and Strategic Implications for Green Finance - Fucà, Romina; Cubico, Serena; Ardolino, Piermatteo; Rosiello, Francesco (Frontiers in Law, 2024)
This paper examines the integration of Sustainable Material Culture (SMC) within the Green Finance (GF) framework, focusing on decision-making strategies inspired by game theory, inference rules, and advanced financial modeling to support sustainable economic principles. Since the 2008 financial crisis, traditional investment strategies have increasingly sought alignment with long-term sustainability goals. However, they inherently carry risks when adapting to the evolving complexities of environmental challenges, such as biodiversity loss, climate change, and infrastructure inequity. SMC is defined here as the material objects, practices, and frameworks reflecting human efforts to promote sustainability, driven by individual and collective investments. Our analysis identifies significant challenges in GF, such as the dual roles of investors as contributors to and beneficiaries of SMC, alongside the application of advanced decision-making frameworks, including Pareto efficiency and Bayesian-Nash equilibrium, to support these roles effectively. We explore how GF initiatives, exemplified by global sustainable finance instruments, address (and sometimes struggle to meet) the multidimensional requirements of SMC. We illustrate how these investments foster economic transformation and resilience by building on case studies of innovative GF initiatives—including sovereign green bond issuances, community-led projects, and energy transition programs in emerging markets. Nuanced trade-offs between commissions and omissions by stakeholders highlight the ethical challenges in designing and promoting sustainable financial products.